Fostering Interprofessional Geriatric Patient Care Skills for Health Professions Students Through a Nursing Facility-Based Immersion Rotation - Laura K. Byerly; Leslie C. Floren; Michi Yukawa (Association of American Medical Colleges, 2020)
Introduction Interprofessional (IP) clinical care is ideally taught in authentic environments; however, training programs often lack authentic opportunities for health professions students to practice IP patient care. Skilled nursing facilities (SNFs) can offer such opportunities, particularly for geriatric patient care, but are underutilized as training sites. We present an IP nursing facility rotation (IP-SNF) in which medical, pharmacy, and physical therapy students provided collaborative geriatric patient care. Methods Our 10-day immersion rotation focused on four geriatric competencies common to all three professions: appropriate/hazardous medications, patient self-care capacity, evaluating and treating falls, and IP collaboration. Activities included conducting medication reviews, quarterly care planning, evaluating functional status/fall risk, and presenting team recommendations at SNF meetings. Facility faculty/staff provided preceptorship and assessed team presentations. Course evaluations included students' pre/post objective-based self-assessment, as well as facility faculty/staff evaluations of interactions with students. Results Thirty-two students (15 medical, 12 pharmacy, five physical therapy) participated in the first 2 years. Evaluations (n = 31) suggested IP-SNF filled gaps in students' geriatrics and IP education. Pre/post self-assessment showed significant improvement (p < .001) in self-confidence related to course objectives. Faculty/staff indicated students added value to SNF patient care. Challenges included maximizing patient care experiences while allowing adequate team work time. Discussion IP-SNF showcases the feasibility of, and potential for, engaging learners in real-world IP geriatric patient care in a SNF. Activities and materials must be carefully designed and implemented to engage all levels/types of IP learners and ensure valuable learning experiences.